Structural and optical properties of pseudobinary wurtzite alloy nanowires - Kwon, S.J.; Choi, Y.-J.; Choi, K.-J.; Kim, D.-W.; Park, J.-G. (Materials Research Society Symposium Proceedings, 2008)
Pseudobinary CdS xSe 1-x and ZnS xSe 1-x (0 ≤ × ≤ 1) alloy nanowires were synthesized on an Au-coated Si substrate by pulsed laser deposition (PLD) process. The synthesized alloy nanowires were single crystalline hexagonal wurtzite structures. Both the lattice constant and the unit cell volume of each alloy nanowire were linearly correlated with the composition, x, and therefore satisfying the Vegard's law. Bandgap of each alloy nanowire measured by photoluminescence (PL) also changed linearly with the composition implying its tunability in the spectral region over a range of 1.75-2.45 eV (CdS xSe 1-x) and 2.66-3.50 eV (ZnS xSe 1-x) with more systematic controllability. This linear scaling behavior of the bandgaps of each alloy nanowire was clearly distinguished from the case of thin films made of the same materials and some case of the ZnS xSe 1-x alloy nanowires reported by another group mainly due to the inner strain relaxation in the confined one-dimensional structure of the nanowires. ？ 2009 Materials Research Society.